Detection of deteriorating technical state of aviation radio electronic devices - Заліський, М. Ю. (Problems of Informatization and Control, 2015)
A procedure for detecting the deterioration of technical state of aviation radio electronic devices inoperation systems considered in the article. Analysis of the detection procedure based onmathematical modeling was carried out, detection characteristics were obtained for a wide range ofinput data